Process for a Free-Standing and Stable All-Metal Structure for Symmetrical Lithium–Oxygen Batteries - Luo, Nan; Ji, Gui-Juan; Wang, Huan-Feng; Li, Fei; Liu, Qing-Chao; Xu, Ji-Jing (ACS nano, 2020)
A number of inherent and thorny obstacles still stand in the way of the practical application of Li–O2 batteries, which require development of an advanced lithium anode and O2 cathode. Herein, the strategy of a symmetrical Li–O2 battery is presented. Specifically, Cu nanoneedle arrays with a nanoengineered Au coating are grown directly on a Cu foam substrate (Au/Cu@FCu), which can act as both the anode backbone and the cathode in a Li–O2 battery. The excellent conductivity, high porosity, large specific surface, and superior lithiophilicity as well as high catalytic activity of the Au/Cu@FCu electrodes can simultaneously regulate the deposition behavior of the lithium metal in the anode and catalyze the formation/decomposition of Li2O2 in the cathode. As a result, the Li uniformly deposited on the Au/Cu@FCu anode without Li dendrites, showing a high Coulombic efficiency over 96% and a long and stable cycle lifetime over 970 h. At the same time, the Au/Cu@FCu cathode demonstrates extremely low overpotentials (0.64 V) and a much higher specific capacity of 27 270 mAh g–1 compared to the Li–O2 batteries with a carbon-free cathode reported to date. Moreover, the “ebb and flow” phenomenon of the anode and cathode morphology is also observed in the Li–O2 battery.